A hybrid composite of H2V3O8 and graphene for aqueous lithium-ion batteries with enhanced electrochemical performance. Issue 34 (10th August 2022) - Duan, Wenyuan; Li, Yanlin; He, Yeming; Xin, Duqiang; Lashari, Najeeb ur Rehman; Ma, Cheng; Zhao, Yuzhen; Miao, Zongcheng
Abstract : Aqueous rechargeable lithium-ion batteries (ARLBs) are regarded as a competitive challenger for large-scale energy storage systems because of their high safety, modest cost, and green nature. Abstract : Aqueous rechargeable lithium-ion batteries (ARLBs) are regarded as a competitive challenger for large-scale energy storage systems because of their high safety, modest cost, and green nature. A kind of modified composite material composed of H2 V3 O8 nanorods and graphene sheets (HVO/G) has been effectively made by a one-step hydrothermal method and following calcination at 523 K. XRD, SEM, TEM, and TG are used to determine the phase structures and morphologies of the composite materials. Owing to the advantage of the layered structure of H2 V3 O8 nanorods, the excellent conductivity of the graphene sheets, and the 3D network structure of the modified composite, the ARLBs with HVO/G can deliver an adequate specific capacity of 271 mA h g −1 at 200 mA g −1 and have a retention rate of 73.4% after 50 cycles. The average discharge capacity of ARLB with HVO/G as anode has a considerable improvement over that of HVO/CNTs and HVO, whatever the current rate used. Moreover, we find that the diffusion coefficient of lithium-ion increases by an order of magnitude through the theoretical calculation for HVO/G ARLB. The new ARLB with HVO/G electrode is a potential energy storage system with great advantages, such as simple preparation, easy assembly process, excellent safety and low-cost environmental protection.